2013
DOI: 10.5812/jjm.7750
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Bacterial Effect of Punica granatum Extracts Against Antibiotic Resistant Pasteurella haemolytica

Abstract: Background: Continuous researches on drugs that solve the problem of growing number of resistant bacteria are important. Objectives: This research aims to investigate the effectiveness of anti-bacterial properties shown by the extracts prepared from different parts of Punica granatum L. (punicaceae), grown in Syria, against Pasteurella haemolytica, which are resistant to all studied antibiotics. Materials and Methods: A total number of 504 samples of dead sheep lungs were investigated for detection of P. haemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…Zone inhibition for these bacteria was 10.5 at minimum and 18 at maximum condition. In the other study on other bacteria Pasteurella haemolytica which also showed the antibacterial effects of P. granatum (pericarp, leaves, flowers, seeds) (20). An old study done in Delhi presented that the flower aqueous extract has antiamoebic activity against E. histolytica at 2mg/ml and 4mg/ml concentrations (21).…”
Section: Discussionmentioning
confidence: 96%
“…Zone inhibition for these bacteria was 10.5 at minimum and 18 at maximum condition. In the other study on other bacteria Pasteurella haemolytica which also showed the antibacterial effects of P. granatum (pericarp, leaves, flowers, seeds) (20). An old study done in Delhi presented that the flower aqueous extract has antiamoebic activity against E. histolytica at 2mg/ml and 4mg/ml concentrations (21).…”
Section: Discussionmentioning
confidence: 96%
“…Hence the present study was planned. [7][8][9][10][11][12][13][14][15][16] These phytochemical components contribute wonderful, economic and eco-friendly effects of pomegranate peel extract. 17 The antidepressant activity of Punica granatum is mentioned in the Indian system of traditional medicine, but there is a rare scientific evidence to prove its activity by Shamima et al 18 Hence, the present study is designed to evaluate the antidepressant activity of Punica granatum peel extract using animal models in mice was planned.…”
Section: Introductionmentioning
confidence: 99%